EFFECT OF PARAMETERS OF MULTIGRID METHOD ASSOCIATED WITH EXTRAPOLATORS IN CFD PROBLEMS - Anunciação, M. A. M.; Pinto, M. A. V.; Araki, L. K.; Martins, M. A.; Gonçalves, S. F. T. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The focus of this work is analyzing the behavior of the following parameters: the iteration error, the processing time (CPU time) and the convergence factors for two problems of Computational Fluid Dynamics (CFD): the two-dimensional linear heat diffusion problem, governed by a Poisson-like equation, with Dirichlet’s boundary conditions, and it is solved by using the Geometric Multigrid Method associated to the following extrapolation methods: Aitken, Empiric, Mitin, Epsilon (scalar and topological), Rho (scalar and topological), Multiple Aitken Extrapolations and Multiple Mitin Extrapolations; and the square lid-driven cavity, governed by Burgers’ equations, with Dirichlet’s boundary conditions, solved by using the Geometric Multigrid associated to the Topological Epsilon Extrapolation Method during the Multigrid cycles. According to numerical results, it was observed: the reduction of the magnitude of iteration error, the reduction of non-dimensional residual based on the initial estimate and the reduction of the convergence factor, with a CPU time compatible to the pure Multigrid Method for both problems.